Effect of Load Eccentricity on the Performance of Skirted Square Shallow Foundations in Dry Sandy Soils (Journal of Engineering, 2025)
The research evaluates the influence of load eccentricity on square shallow foundation behavior when embedded in dry sandy soil at a relative density of soil =30% with and without skirts. Laboratory model tests analyzed a 10 × 10 cm foundation under one central load condition (E/B = 0, where E is the load eccentricity and B is the foundation width) and three eccentric load conditions (E/B = 0.04, 0.08, and 0.16). Three skirt lengths were examined: 0.5B, 1B, and 1.5B.  The results showed that skirted foundations significantly enhanced bearing capacity and reduced settlement compared to unskirted ones. The maximum improvement in bearing capacity occurred under central loading with a skirt length of 1.5B, where the Bearing Capacity Ratio (BCR) reached 4.4 times. Under the highest eccentricity (E/B = 0.16), the BCR decreased to 3.95 times. Settlement was also effectively reduced, with the Settlement Reduction Factor (SRF) reaching 0.921 under central loading and remaining as high as 0.85 under eccentric loading. The results confirm that skirted foundations improve the bearing capacity and reduce settlement of shallow foundations on sandy soils under both central and eccentric loads.